Individuals Who Experience Autonomous Sensory Meridian Response Have Higher Levels of Sensory Suggestibility. (January 2020) - Keizer, Anouk; Chang, Tzu Han (Rebecca); O'Mahony, Cian James; Schaap, Nathalie Solange; Stone, Kayla Dawn
Autonomous sensory meridian response (ASMR) is a self-reported sensory phenomenon that elicits a pleasurable tingling sensation that often starts in the head. This study showed that participants who experience ASMR ( N = 35) are also more prone to experience illusory sensory events than controls ( N = 25), as measured with the Sensory Suggestibility Scale. This suggests that ASMR is not only associated with cognitive traits such as imagery ability but also to how individuals physically experience sensory events.